IMPLEMENTASI KEPEMIMPINAN TRANSFORMASIONAL KEPALA SEKOLAH DI SMA NEGERI 1 BARRU KABUPATEN BARRU - Musdalifah Musdalifah; Arifuddin Siraj; Marjuni Marjuni (Universitas Islam Negeri Alauddin Makassar, 2020)
This study aims to: Describe the implementation of idealized influence of headmaster in SMA Negeri 1 Barru, Barru Regency. This type of research is a qualitative descriptive study. With a phenomological approach. Data were collected through observation, interviews and documentation. Data were analyzed using data reduction methods, data presentation, drawing conclusions and verification. Testing the validity of the data through the credibility test, namely by using triangulation techniques (source, technique, and time) and member check. The results of this study indicate that the implementation of idealized influence of headmaster in SMA Negeri 1 Barru, Barru Regency, namely the involvement of teachers and staff in the field of meeting administration, giving ideas / opinions, forming a team of vision and mission formulation although not optimal teacher self-development because of the large number of teachers, optimal steps. Quality improvement through participatory and policy dissemination and the formation of activity implementers.